Is the ovarian preservation safe in young women with stages IB–IIA villoglandular adenocarcinoma of the uterine cervix? - Ju, U Chul; Kang, Woo Dae; Kim, Seok Mo (Journal of gynecologic oncology, 2018)
Because villoglandular adenocarcinoma (VGA) of the uterine cervix has favorable features and outcomes, patients receive less radical surgery and young women preserve their ovaries. We aimed to evaluate the clinicopathological features and outcomes of VGA and to see if the ovarian preservation is safe in young women with VGA. We retrospectively reviewed medical records and identified patients with VGA, who had been treated and followed from January 2004 to December 2015. This study consisted of 17 patients with VGA, including 9 premenopausal women. International Federation of Gynecology and Obstetrics (FIGO) stage IB1 disease was found in 12 patients (70.6%), IA1 in 2, IA2 in 1, IB2 in 1, and IIA1 in 1. Of the 12 women diagnosed with stage IB1 disease, a young woman received only conization and she has not showed a recurrence. During a median follow-up of 58 months (range: 12-116), 4 patients, who had undergone radical surgery for stage IB1 disease, had a recurrence and one of them died due to disease progression. Among patients with stages IB-IIA disease, 2 premenopausal women did not receive simultaneous oophorectomy or chemoradiation therapy. Both of them had a recurrent tumor at adnexa. This study revealed favorable features and outcomes of VGA. However, the appropriate treatment for young women with early-stage VGA must be cautiously selected. Ovarian preservation might not be safe when young women with stages IB-IIA VGA undergo surgical procedures.